2016
DOI: 10.1091/mbc.e16-04-0226
|View full text |Cite
|
Sign up to set email alerts
|

Contact inhibition of locomotion and mechanical cross-talk between cell–cell and cell–substrate adhesion determine the pattern of junctional tension in epithelial cell aggregates

Abstract: A computational approach is used to analyze the biomechanics of epithelial cells based on their capacity to adhere to one another and to the substrate and exhibit contact inhibition of locomotion. This approach reproduces emergent properties of epithelial cell aggregates and makes predictions for experimental validation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(58 citation statements)
references
References 73 publications
3
55
0
Order By: Relevance
“…We conclude by noting that recently there have been several interesting attempts at extending the Vertex Model description to three dimensions [85, 107112]. While in principle possible, extending the AVM to a curved surface or making it fully three-dimensional would be quite involved.…”
Section: Resultsmentioning
confidence: 96%
“…We conclude by noting that recently there have been several interesting attempts at extending the Vertex Model description to three dimensions [85, 107112]. While in principle possible, extending the AVM to a curved surface or making it fully three-dimensional would be quite involved.…”
Section: Resultsmentioning
confidence: 96%
“…We conclude by noting that recently there have been several interesting attempts at extending the Vertex Model description to three dimensions [85,[107][108][109][110][111][112]. While in principle possible, extending the AVM to a curved surface or making it fully three-dimensional would be quite involved.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we found that genes that showed DNA methylation changes following clozapine treatment were enriched for the GO terms “cell substrate adhesion”, which is essential for cells to interact with their environments [29], and “cell matrix adhesion”, which is essential for cell migration, tissues organization, and differentiation [30]. Similarly, in a recent analysis of differential gene expression profiles in neurons from twins with treatment-resistant SCZ who had discordant responses to clozapine using pluripotent stem (iPS) cell based technology, we found that differentially expressed genes were enriched for “cell adhesion” and “biological adhesion” [6].…”
Section: Discussionmentioning
confidence: 99%